Multi-sensor system for in situ shape monitoring and damage identification of high-speed composite rotors. (August 2016) - Philipp, K.; Filippatos, A.; Kuschmierz, R.; Langkamp, A.; Gude, M.; Fischer, A.; Czarske, J.
Abstract: Glass fibre-reinforced polymer (GFRP) composites offer a higher stiffness-to-weight ratio than conventional rotor materials used in turbomachinery. However, the material behaviour of GFRP high-speed rotors is difficult to predict due to the complexity of the composite material and the dynamic loading conditions. Consequently dynamic expansion measurements of GRFP rotors are required in situ and with micron precision. However, the whirling motion amplitude is about two orders of magnitude higher than the desired precision. To overcome this problem, a multi-sensor system capable of separating rotor expansion and whirling motion is proposed. High measurement rates well above the rotational frequency and micron uncertainty are achieved at whirling amplitudes up to 120µm and surface velocities up to 300 m/s. The dynamic elliptical expansion of a GFRP rotor is investigated in a rotor loading test rig under vacuum conditions. In situ measurements identified not only the introduced damage but also damage initiation and propagation. Abstract : Highlights: Damage progression of rotors can be determined by dynamic expansion measurements. The tumbling motion of the rotor limits achievable measurement uncertainties. Algorithms for elliptical expansion enable improved measurement precision. The cross-sensitivity of rotor expansion regarding tumbling motion is eliminated.